(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Serum prolactin (PRL) level is important for differentiating prolactinomas from non-functioning pituitary adenomas (NFPAs). However, extremely high PRL levels in patients with large pituitary tumors can lead to the high-dose hook effect, resulting in falsely low assay readings. PRL measurement after serial dilution may overcome this problem. Objective: To evaluate the implications of PRL measurements before and after serial dilution in patients with pituitary macroadenomas. Methods: This cross-sectional study included 73 patients with pituitary macroadenomas admitted to the Department of Neurosurgery at the National Institute of Neurosciences, Dhaka. Clinical, biochemical, and radiological characteristics were recorded. Serum PRL was measured by chemiluminescent immunoassay after 1:10 and 1:100 dilutions. Agreement between PRL levels preand post-dilution was assessed using the kappa statistic. Results: The mean age of the participants was 42.0±12.3 years; 28.8% were female. Headache and visual disturbances were common symptoms. Tumor size averaged 3.3±1.0 cm (maximal diameter), with 28.8% classified as giant tumors. Dilution assays revealed that three patients (4.1%) initially categorized as having PRL <200 ng/mL exhibited significantly elevated levels (>200 ng/mL) post-dilution. All affected patients had tumors with suprasellar extension. In addition, seven patients who were reported to have PRL levels>200 ng/mL in undiluted serum had markedly high PRL (606-12582 ng/mL) when measured after dilution. Moderate agreement was found between pre- and post-dilution PRL levels (κ=0.557, p<0.001). Conclusion: Serial dilution uncovered clinically meaningful underestimation of serum PRL in a subset of patients, emphasizing the persistent relevance of the hook effect even with modern assays. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 66-71